Pemilihan Staff Pengajar Terbaik dengan Menggunakan Metode Preference Selection Index - Atsauri, Muhammad Riki (Jurnal Sains dan Teknologi Informasi, 2025)
Selecting the best teaching staff is crucial in the education sector, as it motivates teachers who have educated students and can be recognized for their contributions. However, the data collection process is currently poorly organized, resulting in less than optimal selection of the best teaching staff. Therefore, the author used a decision support system using the Preference Selection Index (PSI) method to calculate competency scores for each teaching staff member and to rank them accordingly. The PSI method does not require relative importance between attributes. This method is used when determining relative importance between attributes is problematic. A decision support system implementing the PSI method is expected to assist in selecting the best teaching staff. This research can assist in making decisions regarding the selection of the best teaching staff accurately, effectively, and in a structured manner. The results of the study in determining the best teaching staff resulted in the best alternative, A3, with a score of 1.0000, thus being the best teaching staff member.